2022
DOI: 10.1002/ab.22052
|View full text |Cite
|
Sign up to set email alerts
|

Why do we share aggressive online content? Testing a short cycle model

Abstract: The present study aimed to observe the impacts of aggressive online content exposure and personality on aggressive content sharing, considering the mediating role of positive and negative affects. A total of 302 Brazilians, equally divided into two groups, participated in a social network simulation, being exposed to aggressive (experimental group) or neutral (control group) posts and choosing what they would like to share on this site (among aggressive or nonaggressive material). A factorial MANOVA showed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…The present study expands on this statement, indicating that this impact can occur in negative emotions, subsequently increasing the likelihood of aggression. Previous studies with GAM also corroborate this mediation of emotions in the effects on aggressive behavioral tendencies (e.g., Barlett & Anderson, 2012;Cavalcanti & Pimentel, 2016;Santos et al, 2022). Future studies can further investigate this mediation using longitudinal and experimental designs.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The present study expands on this statement, indicating that this impact can occur in negative emotions, subsequently increasing the likelihood of aggression. Previous studies with GAM also corroborate this mediation of emotions in the effects on aggressive behavioral tendencies (e.g., Barlett & Anderson, 2012;Cavalcanti & Pimentel, 2016;Santos et al, 2022). Future studies can further investigate this mediation using longitudinal and experimental designs.…”
Section: Discussionsupporting
confidence: 63%
“…Studies using GAM have consistently demonstrated that violent media (that depicts any form of aggression) is one of the risk factors for aggressive behavior, both directly after exposure (e.g., Bushman & Anderson, 2002; Santos et al, 2022) and increasing trait aggression (e.g., Anderson, Bushman, et al, 2017; Miles‐Novelo et al, 2022). However, when the focus is superhero media, mixed results are found.…”
Section: Introductionmentioning
confidence: 99%